PENGEMBANGAN VIDEO TUTORIAL PADA MATA KULIAH PENGANTAR STATISTIKA PENDIDIKAN UNTUK PEMBELAJARAN E-LEARNING - Raharjo Raharjo (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2014)
This study aims to produce a product video tutorials on introductory statisticscourse of education for e-learning in Civics Program S1 UNJ FIS. The method used is the method of Development and Research (R & D). The study produced a video tutorial and a website for e-learning in introductory statistics courses of education with the name of the website http://statistikapendidikan.com. The study found that in this way the quality of teaching and learning outcomes can be improved with either. From the results of the feasibility test/quality video tutorials for e-learning through the website http://statistikapendidikan.com obtained the average number of 3.89 with good category.